Looking beyond psychosocial adversity and sex: Clinical factors associated with ADHD and other psychiatric disorders in a non-Caucasian sample of high-risk siblings (2024)
ABSTRACT: This study examined the association of clinical factors, independent of sex and high psychosocial adversity (HPAd), with the presence of ADHD or other mental disorders, specifically within a middle-income country with a non-Caucasian population. A multi-centric cross-sectional study was conducted in three sites in Colombia. Our study recruited trios of an ADHD proband, one sibling, and one parent. We used valid instruments for assessing parents and siblings. The sample included 223 siblings, an average age of 12.3 (SD 3.9), and 51.1% Females. The ADHD recurrence risk ratio (λ) was 12. The clinical factors mainly associated with the presence of ADHD, independent of sex and HPAd, were 1) Pregnancy and childbirth complications, 2) Delayed psychomotor development, 3) Temperament, and 4) Sleep disturbances. Our research showed that, independently of HPAd and the male sex, there were other clinical factors associated with ADHD and other psychiatric disorders in this population. These findings need to be replicated in similar populations globally.